USING OF DIGITAL EDUCATIONAL ENVIRONMENT FOR TEACHING MARITIME ENGLISH TO FUTURE SHIP MECHANICS - Diahyleva Олена; Yurzhenko Альона; Kononova Олена (Journal of Information Technologies in Education (ITE), 2023)
The article is devoted to the organization of the process of teaching General English to future ship – engineers as an important and compulsory part in the digital environment of maritime educational institutions. Such virtual environment is a combination of the usage of digital technologies and tools in teaching and learning that can improve the efficiency of the English language learning process. Since the digital environment is not limited to time or attached to a place, it is more flexible, more individualized and more mobile than traditional forms of education. An example of a digital environment is presented on the LMS Moodle. The advantages of using this platform are listed in the work. The research uses several methodological tools, namely: analysis, synthesis, comparison, abstraction and deduction. The Maritime English course is one of the first steps for cadets of the ship -engineering department on the way for building communicative competence. Today, the labor market requires a competent graduator who is able to perform his duties in the engine room. Qualified ship - engineers must have adequate knowledge of English language for a specific purpose, for communication in an international crew. A variety of e-course tools are used to make their communication clear and understandable. The article also provides examples of H5P tasks (advent calendars, audio recordings, flipping text cards, instant feedback dictation, drag-and-drop text tasks, word highlighting, etc.). The types of content that can be created in the H5P format are listed in the article. The study was conducted on the basis of the third course of the ship – engineering department of Kherson State Maritime Academy. The main goal of the experiment was the formation of communicative competence of future ship – engineers using the digital environment of a maritime educational institution. The results of the experiment confirmed the positive impact of using the digital environment on the communicative competence of future ship – engineers. As a result, it was established that an interactive approach to the organization the learning process is the most effective compared to other methods, the process of learning a foreign language and increases its effectiveness. Further research is also planned to be devoted to the use of the flipped classroom when teaching maritime English to future ship - engineers in modern maritime higher education institutions.